Methodological Aspect of Mortars Dating (Poznań, Poland, MODIS). Issue 6 (28th December 2017) - Michalska, Danuta; Czernik, Justyna; Goslar, Tomasz
ABSTRACT: An accurate radiocarbon ( 14 C) dating of mortars requires adjusting the sample preparation procedure to each specific mortar composition. In order to follow the influence of mortar components and the preparation procedure on dating results, a mortar intercomparison study (MODIS) was undertaken by 10 organizations (institutes and laboratories) in the analyses of four different types of mortars (see in this issue Hajdas et al. 2017 and Hayen et al. 2017). This paper presents the preparation protocol DoM v.1 applied by the Poznań team, together with dating results on a set of mortar samples used for the of intercomparison. This procedure involved petrographic observations, SEM-EDS analyses, different mechanical-chemical preparation, a test of leaching reaction for available fractions, and finally 14 C dating of chosen samples. The applied preparation allows one to obtain dry-sieved grain fractions and different fractions from suspension: grain fractions from suspension collected in different times of leaching, repeated suspension (different portions), as well as suspension collected at different times of sedimentation. The obtained results show the great importance of good sampling and the influence of sample preparation on 14 C dating results.